Perceptions and Coping Strategies: A Study on Work Life Balance Among Male Civil Engineers in Nepal - Shahi Khadgi, Arbindra; Tamang, Sanjita (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: This study investigates how male civil engineers in Nepal perceive work-life balance and identifies the coping strategies they employ to manage the demands of their profession. Design/methodology/approach: This study utilized a qualitative research approach within the interpretivist paradigm, employing Heidegger’s interpretative phenomenology to explore male civil engineers’ lived experiences with work-life balance. Data were gathered through semi-structured, face-to-face interviews with ten experienced engineers in Kathmandu Valley, focusing on their professional and personal challenges. The analysis followed Benner’s four-step process, and thematized using MAXQDA. Findings: The study highlights that male civil engineers in Nepal achieve work-life balance through a multifaceted approach that encompasses effective management of professional and personal responsibilities and the development of a personal balance philosophy, while addressing challenges from site supervision and project deadlines. Essential coping strategies include utilizing family support, managing time efficiently, prioritizing tasks, mitigating stress, and engaging in task crafting, reinforcing the importance of a dynamic and proactive approach to balance. Conclusions: This study highlights that achieving work-life balance is vital for male civil engineers in Nepal, emphasizing that effective time management and robust family support are essential coping strategies; it also highlights the need for organizations to adopt adaptive HR policies and promote job crafting to address the evolving challenges of engineering responsibilities. Implications: This study highlights the necessity for adaptable theoretical frameworks that reflect the evolving, individualized approaches to work-life balance among male civil engineers. It advocates for organizations and policymakers to implement comprehensive strategies addressing on-site demands, project deadlines, and family support, in order to create flexible work environments and supportive policies that boost employee satisfaction and resilience. JEL Classification: J24, J28, M54